Applicability and management of a scholar projects focused on the english subjects as a teaching strategy to 10th grade students at Daniel Octavio Crespo High School - Beitia, Lineth (UDELAS, 2013)
The implementation of scholar projects work has benefited studens from eduactional institutions in our country and all over the world. Due to the fact that such projects integrate theory and practice through the implementation of teaching strategies that effectively connect the knowledge obtained in the classroom real situations. Once our primary role is to organize and develop educational projects.